Enhancement of Fenton and photo-Fenton processes at initial circumneutral pH for the degradation of the β-blocker metoprolol. (1st January 2016) - Romero, V.; Acevedo, S.; Marco, P.; Giménez, J.; Esplugas, S.
Abstract: The need for acidification in the Fenton and photo-Fenton process is often outlined as one of its major drawbacks, thus in this work the acidification of the Metoprolol (MET) is avoided by the addition of resorcinol (RES), which is used to simulate model organic matter. The experiments were carried out at natural pH (6.2) with different Fe 2+ (1, 2.5, 5, and 10 mg/L) and H2 O2 (25, 50, 125 and 150 mg/L) concentrations. The performance of MET and RES degradation was assessed along the reaction time. Working with the highest concentrations (5 and 10 mg/L of ferrous iron and 125 and 150 mg/L of H2 O2 ) more than 90% of MET and RES removals were reached within 50 and 20 min of treatment, respectively, by Fenton process. However a low mineralization was achieved in both cases, likely, due to by-products accumulation. Regarding to photo-Fenton process, within 3 min with the highest iron and hydrogen peroxide concentrations, a complete MET degradation was obtained and 95% of RES conversion was achieved. Parameters such Total Organic Carbon, Chemical Oxygen Demand, and AOS were measured. Intermediates were identified and MET degradation path was proposed in the presence of resorcinol. Finally, a comparison between Fenton and photo-Fenton processes at acid pH and at initial circumneutral pH was discussed. The positive effect of RES on Fenton and photo-Fenton systems has been confirmed, allowing the work at circumneutral pH. Graphical abstract: Highlights: Fenton and photo-Fenton processes at initial circumneutral pH have been studied. The acidification of the solution was avoided by the addition of resorcinol as organic material. We achieve removals over 90% for metoprolol and resorcinol in both process, Fenton and photo-Fenton. We proposed a variant of Fenton and photo-Fenton using Fe2 SO4 . A propose for estimating near-optimal regions of operability is also studied.